Vertical distribution of heat and momentum flux over east coast of India during Monex-79 (MAUSAM, 1988)
The heat and momentum transport over east coast of Indian subcontinent have been computed using Monex- 79 data. The mean and eddy components due to meridional circulation are separated. These fluxes show remarkable changes with latitude in different layers.